Rock glaciers, protalus ramparts and pronival ramparts in the south-eastern Alps - Colucci, R. R.; Boccali, C.; Žebre, M.; Guglielmin, M. (Geomorphology, 2016)
Rock glaciers and protalus ramparts are characteristic landforms of the periglacial domain often used as markers for the occurrence of permafrost in mountain terrains. As such, relict rock glaciers can be used for paleoclimate reconstructions. We present here the first previously unreported rock glacier inventory of the south-eastern Alps (including the north-eastern-most region of Italy and Slovenia), interpreted from high resolution orthophotos and a high resolution digital terrain model interpolated from airborne laser scanning (LiDAR). We mapped 53 rock glaciers covering a total area of 3.45 km2. The majority of rock glaciers are classified as relict and distributed between 1708 and 1846 m a.s.l. with slope ranging between 19° and 27°. In addition to rock glaciers we observed 66 protalus (pronival) ramparts, having median elevation of 1913 m a.s.l. and covering 0.48 km2. More than half of the inventoried protalus ramparts are located in the more maritime area of the Alps with higher precipitation compared to the location of rock glaciers. Using paleoclimate reconstruction based on the 1981–2010 climatological record of the area, we infer that the rock glaciers formed during one of the dry and cold periods of the late Pleistocene and early Holocene. Possible evolution of the active pronival forms observed in the most maritime area of this alpine sector is also discussed.